Therapeutic rehabilitation for Klippel-Feil syndrome: a case report - Wardah Rauf,; Samia Sarmad,; Sameed Liaqat,; Saleem, Safa; Muhammad Jawad,; Muhammad Ahad, (Journal of the Pakistan Medical Association, 2025)
Klippel-Feil syndrome (KFS) is a genetic condition presenting with a triad of symptoms: short neck, limited range of motion in the neck, and a low posterior hair line. Herein, we report the case of an eight-year-old girl who presented with complaints of pain, numbness, and a triad of KFS at the Paediatric Physical Therapy and Neuro-Rehabilitation Centre, Lahore. The aim of this report is to show that a rare syndrome can be coped very effectively through efficient goal setting. Physiotherapy intervention protocol was designed and given to the patient for four weeks and prognosis was established. Keywords: Klippel-Feil syndrome, Physiotherapy Intervention, Genetic Condition.